2009
DOI: 10.2116/analsci.25.1163
|View full text |Cite
|
Sign up to set email alerts
|

Application of 4-Iodophenol-enhanced Luminol Chemiluminescence to Direct Detection of Horseradish Peroxidase Encapsulated in Liposomes

Abstract: 4-Iodophenol was applied to an enhancer in the direct detection of horseradish peroxidase (HRP) encapsulated in liposomes by using luminol chemiluminescence (CL). Luminol, 4-iodophenol and hydrogen peroxide permeate into the inner phase of liposomes containing HRP, resulting in the progress of 4-iodophenol-enhanced luminol CL catalyzed by HRP in liposomes. The CL intensity observed in liposomes was a factor of 150 greater than that observed in a lipid-free bulk solution. The detection limit in the direct detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…S4A-1 (Supporting Information), showing that reducing the H 2 O 2 concentration retards the CL decay, although the intensity in the initial stage slightly decreases. However, it should be stressed that the novel CL enhancing system established in this study enables the detection of sub-pM HRP without using the so-called enhancer agents, such as p-iodophenol [1,2,[6][7][8][9][10][11][12]19]. At present, the detection of the fM level of HRP has not yet been achieved.…”
Section: Output Versus Picomolar Hrpmentioning
confidence: 99%
“…S4A-1 (Supporting Information), showing that reducing the H 2 O 2 concentration retards the CL decay, although the intensity in the initial stage slightly decreases. However, it should be stressed that the novel CL enhancing system established in this study enables the detection of sub-pM HRP without using the so-called enhancer agents, such as p-iodophenol [1,2,[6][7][8][9][10][11][12]19]. At present, the detection of the fM level of HRP has not yet been achieved.…”
Section: Output Versus Picomolar Hrpmentioning
confidence: 99%
“…The result revealed that the CL intensity observed in liposomes was a factor of 150 greater than a lipid-free bulk solution. Compared with a lipid-free bulk solution, the detection limit in direct detection of HRP encapsulated in liposomes was more sensitive (Kamidate, Maruya, Tani, & Ishida, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The latter when oxidized emits light, following the decay of the excited-state oxidation product. CL intensity can be significantly increased by adding in the substrate solution a molecule that acts as an enhancer, with 4-iodophenol (4-IOP) [4,5] being the most popular enhancer of the HRP-catalysed CL oxidation of luminol. Such enhanced CL reactions provide more intense, prolonged and stable light emission [6].…”
Section: Introductionmentioning
confidence: 99%